کلامِ الٰہی کے کلامِ شعراء پر تفوق کا تحقیقی و تجزیاتی مطالعہ: A Comparative Analytical Study on the Superiority of Divine Speech Over the Speech of Poets - Asrar Ahmed, Dr. Fazail; Saad, Muhammad; Bodla, Muhammad Abdullah (Al-Amīr Research Journal for Islamic Studies, 2024)
The thesis titled "A Comparative Analytical Study on the Superiority of Divine Speech Over the Speech of Poets" investigates the unmatched eloquence of the Quran compared to the eloquence of renowned Arab poets. The study begins by exploring the Quran’s unparalleled rhetorical excellence and linguistic artistry. It then conducts a comparative analysis between the verses of the Quran and the poetry of Imru’ al-Qais, one of the greatest Arab poets.Through detailed examination, the research demonstrates that the divine speech of the Quran surpasses human poetry in eloquence, rhetorical beauty, depth of meaning, and impact on its audience. The study highlights the Quran’s linguistic precision, its ability to convey profound meanings succinctly, and its unmatched rhetorical devices that leave a lasting impression.The research also examines the limitations of human poetry in conveying universal truths and its inability to match the comprehensive nature of the Quranic message. By presenting concrete examples and analytical comparisons, the study substantiates the Quran’s superiority in both form and content.The objective is to provide scholarly evidence of the Quran’s supreme eloquence and highlight the limitations of human speech, reinforcing the Quran’s position as the ultimate source of guidance and wisdom. This analysis underscores the Quran’s literary excellence and its profound significance in Arabic literature. Keywords: Qur’ānic Eloquence, Rhetorical Excellence, Divine Superiority, Comparative analysis, Arabic literature.